2012
DOI: 10.1074/jbc.m111.320929
|View full text |Cite
|
Sign up to set email alerts
|

Selenocysteine Insertion Sequence (SECIS)-binding Protein 2 Alters Conformational Dynamics of Residues Involved in tRNA Accommodation in 80 S Ribosomes

Abstract: Background: Selenocysteine incorporation requires unique translation factors that interact with the ribosome. Results: SECIS-binding protein 2 alters ribosome conformation at two discrete sites. Conclusion: The selenocysteine incorporation reaction requires ribosome modifications in a region known to be required for tRNA accommodation. Significance: Identifying the ribosomal dynamics required for Sec incorporation will enhance our understanding of the translation elongation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Further structural analysis indicated that the C-terminal region in Domain IV of SelB was involved in specific interactions with the bSECIS (37,38). An analogous activating mechanism has been proposed for eEFSec where functional interactions with the ribosome could be driven by SBP2 and the SECIS element (15). By using selective 2-hydroxyl acylation analyzed by primer extension, it was recently discovered that SBP2 causes a conformational change specifically at the Helix 89 on the 28 S ribosomal RNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further structural analysis indicated that the C-terminal region in Domain IV of SelB was involved in specific interactions with the bSECIS (37,38). An analogous activating mechanism has been proposed for eEFSec where functional interactions with the ribosome could be driven by SBP2 and the SECIS element (15). By using selective 2-hydroxyl acylation analyzed by primer extension, it was recently discovered that SBP2 causes a conformational change specifically at the Helix 89 on the 28 S ribosomal RNA.…”
Section: Discussionmentioning
confidence: 99%
“…FLAGeEF1A, FLAG-eEFSec, XH-CTSBP2, and the SECIS element were each added at a final concentration of 1 M. Isolation of total aa-tRNA was performed as above but without the addition of Na 2 [ 75 Se]O 3 . Purification of salt washed 80 S ribosomes from rabbit reticulocyte was performed as described (15). Concentrations of total aa-tRNA and ribosomes in the GTPase activation reactions were at 100 ng/ l and 0.12 M, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…3C). Using the SHAPE strategy, which leads to acylation of accessible 2 ′ OH ribose residues, Caban and Copeland (2012) reported that SBP2 binding to the ribosome altered the reactivity of certain residues encompassing positions C4421 and U4419 in helix H89 and 4080-4166 in ES31L (numbering according to Anger et al 2013). However, our footprinting experiments showed no differences in the accessibilities to hydroxyl radicals of these regions in the 60S•CTSBP2 complex (Supplemental Fig.…”
Section: Sbp2 Contacts the 28s Ribosomal Rrna In The 60s Ribosomal Sumentioning
confidence: 99%
“…Besides, as H89 was found to adopt a conformation change upon CTSBP2 binding (Caban and Copeland 2012), we sought to determine whether CTSBP2 contacts H89. To answer these questions, we analyzed by reverse transcription the 28S rRNA isolated from 80S ribosomes treated by diepoxybutane in the presence of either wild-type CTSBP2 or the SBP2 mutant MutSBP2.…”
Section: Diepoxybutane Cross-linking Validates the Ctsbp2-es7l-e Intementioning
confidence: 99%
See 1 more Smart Citation